The Remains of the Day - Kazuo Ishiguro (Great Britain faber and faber, 1989)
A beautiful and haunting evocation of life between the wars in a great English house. In the summer of 1956, Stevens, the ageing butler of Darlington Hall, embarks on a leisurely holiday that will take him deep into the countryside and into his past.
Keywords: Fiction; Historical fiction; Classics